Tools for the analysis and transformation of medical education and culture for the promotion of mental health in medical students (2019)
Historically, within medical education and in the constitution of organizational structures and medical culture, little emphasis has been placed on the promotion and teaching of inter-personal skills, which is essential to offer a humanised treatment of clinical staff with their patients and their co-workers. Likewise, there have been very few efforts to understand the consequences of the typical pressures of medical training on the living conditions and mental health of students. Therefore, the present narrative review of the literature aims to identify the existing types of curricula and establish their implications, in particular the hidden curricula, and in the appearance of risk factors for mental health in medical students. This reflection serves as a reference when curriculum reforms are being considered in Latin America that aim to transform the teaching of medicine and transform the medical profession. © 2018 Elsevier España, S.L.U.